Installation of rectangular enclosures filled with phase change nanomaterials on the thrombus walls of a residential building to manage solar radiation in different seasons of the year. (1st October 2022) - Abdulkhaliq M Alharbi, Khalid; Aldosari, Obaid; Sina, Nima; Aybar, Hikmet Ş.; Fuxi, Shi; Alkhatib, Samah Elsayed; Allah A Mousa, Abd
Abstract: In this paper, using a numerical method, a room with a Trombe Wall is studied in a period of 10 h in the absence of sunlight. The room is 3 by 4 and 3 m high, with a Trombe Wall on one side. There are 4 barriers on the wall, inside of which PCM is used. This study was performed for PCM discharge mode. This study was arranged for a change in wall thickness from 5 to 45 cm at two inlet air temperatures of 10 and 20 °C and PCM was used. COMSOL-Multiphysics software was used to run this simulation. The use of a thicker Trombe wall raises the average wall temperature throughout the night and also increases the solidification time of PCM within the barriers, according to the findings of this research. PCM solidifies within lower barriers sooner and their temperature is lower. Reducing the inlet temperature to the Trombe wall reduces the freezing time of all PCMs within the barriers and decreases the wall temperature sooner. The maximum operating time of the wall is observed for a wall thickness of 45 cm at 20 °C with inlet air temperature. Highlights: Study of rectangular enclosures filled with phase change nanomaterials. PCM on the thrombus walls of a residential building to manage solar radiation. Change in wall thickness at two inlet air temperatures while examine PCM.